DNA demethylation and tri-methylation of H3K4 at the TACSTD2 promoter are complementary players for TROP2 regulation in colorectal cancer cells - Gehring, Annemarie; Hübner, Kerstin; Rani, H.; Erlenbach-Wünsch, Katharina; Merkel, Susanne; Mahadevan, Vijayalakshmi; Grützmann, Robert; Hartmann, Arndt; Schneider-Stock, Regine (Scientific Reports, 2024)
TROP2 is a powerful cancer driver in colorectal cancer cells. Divergent epigenetic regulation mechanisms for the corresponding TACSTD2 gene exist such as miRNAs or DNA methylation. However, the role of TACSTD2 promoter hypermethylation in colorectal cancer has not been investigated yet. In this study, TROP2 expression strongly correlated with promoter methylation in different colorectal tumor cell lines. Treatment with 5-Azacytidine, a DNMT1 inhibitor, led to demethylation of the TACSTD2 promoter accompanied by an increase in TROP2 protein expression. TROP2 expression correlated with promoter methylation in vivo in human colon tumor tissue, thereby verifying promoter methylation as an important factor in the regulation of TROP2 expression in colorectal cancer. When performing a ChIP-Seq analysis in HCT116 and HT29 cells, we found that TACSTD2 promoter demethylation was accompanied by tri-methylation of H3K4. In silico analysis of GSE156613 data set confirmed that a higher binding of histone mark H3K4me3 around the TACSTD2 promoter was found in TACSTD2 high expressing tumors of colon cancer patients compared to the corresponding adjacent tumor tissue. Moreover, the link between TROP2 and the H3K4me3 code was even evident in tumors showing high intratumoral heterogeneity for TROP2 staining. Our data provide novel evidence for promoter demethylation and simultaneous gains of the active histone mark H3K4me3 across CpG-rich sequences, both being complementary mechanisms in the transcriptional regulation of TACSTD2 in colon cancer. The functional consequences of TROP2 loss in colorectal cancer needs to be further investigated.
CRIS-Team Scopus Importer:2024-02-16